Feasibility of face-to-face and online learning methods to provide nutrition education to midwives, general practice nurses and student nurses. Issue 2 (3rd September 2019) - Lucas, Catherine Jane; Lyell, Ellen; Koch, Britney; Elder, Victoria; Cummins, Leanne; Lambert, Sarah; McMahon, Anne T; Charlton, Karen E
Abstract : Midwives and general practice nurses are ideally positioned to provide nutrition education to pregnant women. However, it appears that they do not receive sufficient nutrition training to enable them to fulfil this role. This study aimed to develop, implement and evaluate a suite of learning resources developed specifically for midwives, general practice nurses and student nurses. A four-module suite of learning resources was developed based on recommendations in the Australian Antenatal Care Clinical Guidelines as well as formative evaluation with stakeholders. The feasibility of these modules was tested using a pre-test and post-test quasi-experimental design with three arms using convenient sampling (face-to-face with midwives; online with student nurses; and online with midwives, nurses and practice nurses). Completion rates across the three study arms were poor (n=40 participants in total). For the combined data, there was a significant increase in knowledge scores across all modules from the pretest score (median (IQR): 3.46 (2.09–4.13)) to the post-test score (5.66 (4.66–6.00)) (p<0.001). Studies of high quality are required to determine if changing the nutrition knowledge and confidence in delivering nutrition care of health professionals results in sustainable changes to their clinical practice.